Nilai-nilai Kepemimpinan Tadulako: Upaya Meningkatkan Tata Kelola Ketahanan Nasional - Makruf, Farid; Ali, Muhammad Nur; Herman, Achmad (Research and Development Agency Ministry of Home Affairs, 2024)
This study aims to explore the importance of Tadulako leadership values in enhancing national governance resilience in Indonesia, particularly in Central Sulawesi. The concept of Tadulako goes beyond individual identity, embodying noble values that promote truth and community welfare. Historically, Tadulako played a significant role in maintaining territorial sovereignty during the colonial period, suggesting that these values are not merely myths but rooted in real struggles for freedom. This study uses an ethnographic approach to examine how these values can serve as an ethical foundation for modern leadership, fostering social cohesion and managing diversity in line with the principle of Bhinneka Tunggal Ika. The results showed that courage, justice, and solidarity are integral to building a cohesive national identity and enhancing social resilience against internal and external threats. This study also emphasized the importance of revitalizing local wisdom and integrating these values into the educational framework to ensure cultural continuity and strengthen community ties. This study is a balanced dialogue between tradition and modernity, showing that principles derived from Tadulako can significantly contribute to a strong and sustainable national resilience strategy. In the context of strengthening national resilience governance, it is recommended that Tadulako leadership values be integrated with the concept of transformational leadership in the modern era. Innovative and flexible leadership that emphasizes adaptability and resilience in facing challenges is essential to maintaining national resilience while realizing the progress of the nation and state.